Readership Survey of the FFA New Horizons Magazine - James J. Connors; Jack Elliot; Kirk Heinze (Journal of Applied Communications, 1994)
The study surveyed readers of the FFA New Horizons magazine to determine reader opinions about magazine usefulness.